Immune Immunomodulation in Coronavirus Disease 2019 (COVID-19): Strategic Considerations for Personalized Therapeutic Intervention. (1st July 2020) - Hall, Mark W; Joshi, Ila; Leal, Luis; Ooi, Eng Eong
Abstract: We are learning that the host response to severe acute respiratory syndrome coronavirus 2 ( SARS-CoV-2) infection is complex and highly dynamic. Effective initial host defense in the lung is associated with mild symptoms and disease resolution. Viral evasion of the immune response can lead to refractory alveolar damage, ineffective lung repair mechanisms, and systemic inflammation with associated organ dysfunction. The immune response in these patients is highly variable and can include moderate to severe systemic inflammation and/or marked systemic immune suppression. There is unlikely to be a "one size fits all" approach to immunomodulation in patients with coronavirus disease 2019 (COVID-19). We believe that a personalized, immunophenotype-driven approach to immunomodulation that may include anticytokine therapy in carefully selected patients and immunostimulatory therapies in others is the shortest path to success in the study and treatment of patients with critical illness due to COVID-19. Abstract : There is unlikely to be a "one size fits all" approach to immunomodulation in patients with COVID-19. Clinical trials of immunomodulators in this setting should include prospective immunophenotyping and should adapt to the dynamic nature of the host immune response.